Pyrosequencing to determine the influence of fallow period on soil microbial communities in the Bolivian highlands - Gomez, Lorena; Jumpponen, Ari M.; Gonzales, Miguel A.; Cusicanqui, Jorge; Valdivia, Corinne; Motavalli, Peter; Herman, Michael A.; Garrett, Karen A. (My University, 2011)
In the Bolivian highlands (Altiplano; approx. 4000 masl), traditional fallow periods are being shortened in an effort to increase short-term crop yields, which may be at the expense of soil quality and plant health. Using 454-pyrosequencing and DNA-tagging, we characterized the response of the microbial community to (1) the length of fallow period and (2) the presence of Parasthrephia sp. and Baccharis sp. (both locally known as „Thola‟), considered beneficial to the maintenance of soil health in fallow fields in this region. The two study regions, Umala and Ancoraimes, differ in their soil characteristics, which may be a fundamental reason for the inherent differences in regional management practices. Soils in Ancoraimes have higher levels of organic matter, nitrogen and other macronutrients, which supported more diverse fungal communities (P<0.001). The presence of Thola after ten years of fallow had a positive effect on soil fungal diversity. Unexpectedly, the longer fallow periods were associated with lower fungal richness and diversity, perhaps because some fields with longer fallow periods were perceived by managers to have lower quality soils. Analyses of bacterial communities and fungal community composition are underway. Our results suggest that the drivers of microbial richness may be more complex than predicted by fallow period alone, and that plant cover may be important in conserving microbial communities.
Keywords: DNA pyrosequencing; Soil microbial communities; Fallow period; Bolivian highlands